SPS621 : Critical thinking and science process skills / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2017)
This course provides an in-depth exposure of skills that focus on scientific skills, which include science process skills and manipulative skills, and thinking skills, particularly high-level thinking skills in scientific reasoning skills. The emphasis of the course is on how those skills can be integrated in teaching explicitly to students lastly, to enable the construction of scientific skills and think more effectively